Reclaiming Freedom in Play: A Critical Review of Early Childhood Education Discourse - Salsabila Rizqi Ramadhanty Alisa, Salsa; Kurniawati Sugiyo Pranoto, Yuli; da Ary, Deasylina; Formen, Ali (Universitas Nahdatul Ulama Surabaya, 2025)
This study critically examines how the concept of Free Play has been constructed, represented, and contested within early childhood education (ECE) discourses between 2019 and 2025. Using a Critical Literature Review grounded in Teun A. van Dijk’s Critical Discourse Analysis (CDA), this study investigates how language and ideology shape understandings of play, freedom, and childhood across global and local contexts, not only as a methodological approach but also as a form of critical ideology deconstruction. 25 peer-reviewed articles were analyzed from Scopus, Taylor & Francis, ERIC, and SINTA databases, focusing on themes of play-based learning, child agency, and educational policy. Findings reveal four dominant themes. First, the academicization and instrumentalization of play illustrate how play is reframed as a tool for academic achievement, reducing its intrinsic value. Second, the negotiation of teacher authority and child agency highlights the tension between adult control and children’s autonomy in play-based settings. Third, cultural contextualization of play demonstrates that meanings of play are embedded within moral and social values, differing across Western and non-Western traditions. Lastly, the ideological reconstruction of freedom exposes how policy rhetoric about autonomy and creativity often conceals regulatory control through assessments and standards. This study concludes that Free Play operates as a contested discursive field shaped by educational ideologies, institutional pressures, and cultural contexts. Reclaiming freedom in play requires reorienting pedagogy toward child-centered practices that value agency, participation, and human dignity. The findings offer implications for educators and policymakers seeking to align early education with democratic and inclusive values